2011
DOI: 10.1074/jbc.m110.204412
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Topological Analysis of Yeast Acyl-CoA:Diacylglycerol Acyltransferase 2, an Endoplasmic Reticulum Enzyme Essential for Triacylglycerol Biosynthesis

Abstract: Acyl-CoA:diacylglycerol acyltransferase (EC 2.3.1.20) is a membrane protein present mainly in the endoplasmic reticulum. It catalyzes the final and committed step in the biosynthesis of triacylglycerol, which is the principal repository of fatty acids for energy utilization and membrane formation. Two distinct family members of acyl-CoA:diacylglycerol acyltransferase, known as DGAT1 and DGAT2, have been characterized in different organisms, including mammals, fungi, and plants. In this study, we characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 39 publications
4
116
1
Order By: Relevance
“…The amino acid sequences of JcDGAT1 and JcDGAT2 are 67 and 56% similar to the corresponding orthologues from Arabidopsis (At2 g19450 and At3 g51520, see Stone et al 2006;Liu et al 2011). Genomic structure analysis showed that JcDGAT1 (JQ319812) contains 16 exons and 15 introns, while JcDGAT2 (JQ319813) contains nine exons and eight introns.…”
Section: Cloning Gene Structure and Phylogenetic Analysis Of Jcdgat1mentioning
confidence: 96%
“…The amino acid sequences of JcDGAT1 and JcDGAT2 are 67 and 56% similar to the corresponding orthologues from Arabidopsis (At2 g19450 and At3 g51520, see Stone et al 2006;Liu et al 2011). Genomic structure analysis showed that JcDGAT1 (JQ319812) contains 16 exons and 15 introns, while JcDGAT2 (JQ319813) contains nine exons and eight introns.…”
Section: Cloning Gene Structure and Phylogenetic Analysis Of Jcdgat1mentioning
confidence: 96%
“…1). Pathways i-iii have been claimed to occur at the lumenal side of the secretory pathway based on biochemical data and bioinformatic analysis of the location of conserved motifs [27,29,[40][41][42][43]. This report makes it likely that also the degradation via alkaline ceramidases occurs lumenally.…”
mentioning
confidence: 94%
“…After 10 min on icewater the derivatization of target proteins was visualized by SDS-PAGE and Western blotting using anti-V5, anti-FLAG and anti-Kar2p antibodies for detection of, Ypc1p, Gpi8p and Kar2p, respectively. Alternatively, we performed SCAM TM assays using NEM adapting protocols described previously [27,28]. For this, microsomes (100 g of protein) were incubated with NEM for 30 min on ice-water unless indicated otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more than 40% of the total amino acid residues are hydrophobic (Table 3). Yeast was the preferred host for DGAT expression (Bouvier-Nave et al, 2000;Burgal et al, 2008;Cao et al, 2010;He et al, 2004;Kalscheuer et al, 2004;Kalscheuer & Steinbuchel 2003;Kroon et al, 2006;Liu et al, 2011;Liu et al, 2010;ManasFernandez et al, 2009;Mavraganis et al, 2010;Milcamps et al, 2005;Nykiforuk et al, 2002;Quittnat et al, 2004;Shockey et al, 2006;Siloto et al, 2009;Wagner et al, 2010;Xu et al, 2008;Yu et al, 2008) followed by insect cells (Buszczak et al, 2002;Cases et al, 1998;Cases et al, 2001;Lardizabal et al, 2001). A limited number of reports used other host cells including E. coli (Saha et al, 2006;Siloto et al, 2008;Weselake et al, 2006) and human cells (Cheng et al, 2001).…”
Section: Recombinant Dgat Expression Updatementioning
confidence: 99%